Parentalidade na perda gestacional : o tempo de luto para o retorno às atividades profissionais - aspectos emocionais e legais - Glaucia Maria Moreira Galvão (2021)
The paid rest for women, according to Brazilian law, related to cases of gestational loss with less than 22 weeks, is it equivalent to two weeks. Regarding the father, we have no labor license in this situation, which accentuates gender inequality. With the use of semi-structured interviews, this work addresses the emotional conditions of mothers and their experiences, evaluating if they can return to professional activities after spontaneous pregnancy loss. The father’s emotional conditions to maintain their usual work routine, seen from the eyes of their partners was also an object of investigation. Some fathers also gave testimonies expressing their grief during the process. Guiding questions were used to verify their perception on the moment they went through. These questions were related to their adaptation of routine, their mourning, and the quality of their own professional practice. After analysing the testimonies and their respective meanings, eight categorizations emerged: symptoms of grief; time to return to work and routine; non-recognition of mourning by society; grief and spirituality; caregiver (hospital) / patient relationship; paternal pain; the need of wanting someone with you; Who is this baby. Some of the strategies bereaved mothers used in order to cope, were seeking support in religion and in work. During the interviews, some feelings were highlighted: loss of control over one’s life; shattered dreams; feeling of incompleteness; guilt and personal defeat; and feelings of being considered “less of a Woman” by society’s eyes. A labor vulnerability was shed to light, with regard of assisting the fathers in their grief during the gestational loss, a pain that is neither recognized nor legally supported. For women, the loss was not only of their babies, there was also subjective loss, loss of identity, loss of ideal, eroticism and their role as women. The women’s resolution towards themselves, to other women, motherhood, the ideal of a woman, among others, are significant themes, that lead the opening for a space of further investigation in how to approach and deal with gestational mourning.